Regulation of blood flow in Paget's disease of bone. - Heistad, D D (1975)
Previous studies have demonstrated an increase in blood flow to extremities involved by Paget's disease of bone. It has been assumed that the increase in blood flow is through bone, but warmth of skin overlying Pagetic bone suggests that cutaneous blood flow might be increased. In three patients with Paget's disease involving one extremity, we compared blood flow in "Pagetic" extremities with flow in the contralateral normal extremities. Resting blood flow (measured with water plethysmographs) was 14.2plus or minus2.9 (meanplus or minusSE) ml/min times 100 ml extremity in the Pagetic limbs. The contribution of cutaneous flow to the increase in extremity blood flow was evaluated with epinephrine iontophoresis, which suppresses flow to skin but not to underlying tissue. Epinephrine iontophoresis of the Pagetic extremities decreased blood flow from 14.2plus or minus2.9 to 3.6plus or minus1.5 ml/min. Local heating (which increases cutaneous flow only) failed to increase blood flow in the Pagetic extremities as much as it did in the normal extremities. This suggests that cutaneous vessels in the Pagetic extremities were already dilated. During heating, blood flow in the normal extremities was similar to resting flow in the Pagetic extremities; this indicates that increases in cutaneous flow could account for most of the increase in total blood flow in the Pagetic extremities. Adrenergic control of blood flow to the Pagetic extremities was compared with that of the normal extremities. Vasoconstrictor responses to reflex stimuli in the Pagetic extremities were reduced; when vasoconstriction occurred it was gradual and sustained after termination of the stimuli, which suggests an exaggerated humoral response but reduced neural response to the stimuli. Intravenous epinephrine produced vasoconstriction in the Pagetic extremities and vasodilatation in the normal extremities. In summary, responses to epinephrine iontophoresis and heating suggest that the increase in blood flow in Pagetic extremities is primarily the result of cutaneous vasodilatation.